The Readiness Indicators for Special Ability Child Educational Management of The Kindergarten Provincial School - Raethong, Saksit; Intarak, Prasert (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to study 1) the readiness indicators for special ability child educational management at the kindergarten provincial school; and 2) the confirmation of the readiness indicators for special ability child educational management at the kindergarten provincial school is descriptive research. The sample group consisted of 70 provincial kindergartens. The data were analyzed using corroborative factor analysis and the statistical indicators used in the data analysis consisted of frequency, percentage, mean, arithmetic mean, standard deviation, corroborative component analysis, and content analysis The findings of this study revealed that: 1. The readiness indicators for special ability child educational management in the kindergarten provincial school composed of 8 dimensions and 56 indicators: 1) the dimension of cooperative among school, parents and related sections, composed of 7 indicators, 2) the dimension of specialize person, composed of 6 indicators, 3) the dimension of curriculum and instruction, composed of 8 indicators, 4) the dimension of planning for children with special ability, composed of 9 indicators, 5) the dimension of systemic of data and information, composed of 7 indicators, 6) the dimension of media and technology readiness, composed of 7 indicators, 7) the dimension of school plant and budgeting composed of 5 indicators, and 8) the dimension of evaluation for development and auditing, composed of 7 indicators, and 2. The confirmation of components and readiness indicators for special ability child educational management the kindergarten provincial school found out that all experts consensus that 8 dimensions, 56 indicators were accuracy, appropriately, possibility, and utility.